The hired girl - Schlitz, Laura Amy (Candlewick Press, 2015)
Fourteen-year-old Joan Skraggs, just like the heroines in her beloved novels, yearns for real life and true love. But what hope is there for adventure, beauty, or art on a hardscrabble farm in Pennsylvania where the work never ends? Over the summer of 1911, Joan pours her heart out into her diary as she seeks a new, better life for herself -- because maybe, just maybe, a hired girl cleaning and cooking for six dollars a week can become what a farm girl could only dream of -- a woman with a future. (Inspired by the author's own grandmother's journal.)